Culprit or Bystander: Defective Mitophagy in Alzheimer’s Disease - Xie, Chenglong; Aman, Yahyah; Adriaanse, Bryan A.; Cader, M. Zameel; Plun-Favreau, Hélène; Xiao, Jian; Fang, Evandro F. (Frontiers in Cell and Developmental Biology, 2020)
Mitophagy is a selective engulfment and degradation of damaged mitochondria through the cellular autophagy machinery, a major mechanism responsible for mitochondrial quality control. Increased accumulation of damaged mitochondria has been observed in the Alzheimer’s disease (AD) human brain, although underlying mechanisms remain largely unknown. Recent studies indicate impaired mitophagy may contribute to the accumulation of damaged mitochondria in cross-species AD animal models and in AD patient iPSC-derived neurons. Studies from AD animals highlight feed-forward vicious cycles between defective mitophagy, and the principal AD pathological hallmarks, including amyloid-β plaques, tau tangles, and inflammation. The concomitant and intertwined connections among those hallmarks of AD and the absence of a humanized AD model that recapitulates disease hallmarks, present a challenge on how to determine whether defective mitophagy is an early event preceding and causal of Tau/Aβ proteinopathies or a bystander. Whilst further studies are required to understand these relationships, targeting defective mitophagy holds promise as a new therapeutic strategy for AD.